An integrated marketing communications campaign on CD Jeans - Urriquia, Aileen Manikad (Animo Repository, 2010)
Direct selling industry remains to be in healthy position even in the midst of the global economics crisis. In the Philippines, this booming industry has caught the interests of new local and multinational companies that are now entering the direct selling market. While the other companies are thiving, CD Jeans has been losing its dealers and buyers to competition. This integrated marketing communication plan is designed for CD Jeans Direct Sales. The company has been in the industry for almost two decades now. From a simple manufacturer of t-shirts and blouses, CD Jeans has grown to be one of the biggest direct selling companies in Metro Manila. Currently, CD Jeans offers a wide array and fortified product lines encompassing apparels, underwear garments, footwear and accessories catering for both women and men. Despite the broad product lines and increased in popularity of the direct selling industry, CD Jeans failed to cope with the emergence of aggressive competitors. These competitors sprout almost everywhere in the Metro Manila leaving CD Jeans with a very small market share. This plan aims to create greater awareness and ultimately increase sales for CD Jeans. The plan includes a promotions opportunity analysis strategies, IMC objectives as well as all relevant outdoor advertising, printed collaterals, mobile and internet marketing and events and sponsorship. The campaign narrows it attack through the use of cost efficient and visually-appealing creative. The thrust of the campaign lies heavily on outdoor advertisements which are designed to reach the commuters which are the primary target. The campaign also bank on the increasing use of internet and mobile, employing mobile and internet marketing to reach the target market specifically those in their early 20s. This integrated marketing communication plan targets two markets the consumers as the primary and dealers as the secondary. Since CD Jeans directly transacts with dealers, it is important to have a two-pronged approach, with a different attacks specific for the dealer while focusing on the consumers. The budget allotted for this campaign can be considered as costly as increasing brand awareness as one of the objectives, would require investment for the company. In addition, a year-long plan is required to achieve the set objectives in this campaign.